(lnx+1)(lnx-1)=0

Simple and best practice solution for (lnx+1)(lnx-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (lnx+1)(lnx-1)=0 equation:


Simplifying
(lnx + 1)(lnx + -1) = 0

Reorder the terms:
(1 + lnx)(lnx + -1) = 0

Reorder the terms:
(1 + lnx)(-1 + lnx) = 0

Multiply (1 + lnx) * (-1 + lnx)
(1(-1 + lnx) + lnx(-1 + lnx)) = 0
((-1 * 1 + lnx * 1) + lnx(-1 + lnx)) = 0
((-1 + 1lnx) + lnx(-1 + lnx)) = 0
(-1 + 1lnx + (-1 * lnx + lnx * lnx)) = 0
(-1 + 1lnx + (-1lnx + l2n2x2)) = 0

Combine like terms: 1lnx + -1lnx = 0
(-1 + 0 + l2n2x2) = 0
(-1 + l2n2x2) = 0

Solving
-1 + l2n2x2 = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + l2n2x2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + l2n2x2 = 0 + 1
l2n2x2 = 0 + 1

Combine like terms: 0 + 1 = 1
l2n2x2 = 1

Divide each side by 'n2x2'.
l2 = n-2x-2

Simplifying
l2 = n-2x-2

Take the square root of each side:
l = {-1n-1x-1, n-1x-1}

See similar equations:

| -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 | | 1059/10=18/1(14/13x) | | -1=-7x | | 6.2h-0.4=2.7 | | 3a+18=3(2a+3) | | X^2+12x-43=4x+5 | | -2=-7x | | -4x+6x^2+5x= | | -7.38=2.05-7.38 | | 4y+8=-2y+1 | | 24Y=72 | | 2.7+10m=7.23 | | 3a-3a^2= | | 2(x+4)+x=11 | | 16x+10=15x+2 | | 3=-4x-6 | | 1=10p | | 7(-1m)=-98 | | .36=ln(x) | | x^2=5x^2+20x+40 | | 5a+3b-6c+2a-4b+13c= | | 8(4p)=-277 | | 4x-15=3x-6 | | -13=7+4x |

Equations solver categories